A software framework for FCC studies: status and plans - Cervantes Javier; Faltova Jana; Ganis Gerardo; Helsens Clement; Hrdinka Julia; Neubüser Coralie; Pezzotti Lorenzo; Selvaggi Michele; Tehrani Niloufar A.; Volkl Valentin; Zaborowska Anna (EPJ Web of Conferences, 2020)
The Future Circular Collider (FCC) is designed to provide unprecedented luminosity and centre-of-mass energies. The physics reach and potential of the different FCC options e+e−, pp, ep, has been studied and published in dedicated Conceptual Design Reports (CDRs) at the end of 2018. Conceptual detector designs have been developed for such studies and tested with a mixture of fast and full simulations. The investigations for all options have been conducted using a common software framework called FCCSW. In this paper, after summarising the improvements implemented in FCCSW to achieve the results included in the CDRs, we will present the current development plans to support the continuation of the physics potential and detector concept optimisation studies in view of future strategic decisions, in particular for the electron-positron machine.